2002
DOI: 10.1086/337919
|View full text |Cite
|
Sign up to set email alerts
|

DeepROSATHRI Observations of the NGC 1399/NGC 1404 Region: Morphology and Structure of the X‐Ray Halo

Abstract: We present the analysis of a deep (167 ks) ROSAT HRI observation of the cD galaxy NGC 1399 in the Fornax cluster, comparing it with previous work on this galaxy and with recent Chandra data. We find, in agreement with previous observations, an extended and asymmetric gaseous halo with a luminosity (in the 0.1-2.4 keV energy band) of L X = (5.50±0.04)×10 41 erg s −1 within 46 kpc (assuming a distance of D=19 Mpc). Using both HRI and, at larger radii, archival PSPC data, we find that the radial behavior of the X… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
177
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(206 citation statements)
references
References 68 publications
(114 reference statements)
27
177
2
Order By: Relevance
“…The velocity dispersions of the PNe are consistent with the values derived by the star's kinematics and with those for the red GCs (Napolitano et al 2002;McNeil et al 2010). The X-ray data have shown the presence of a hot gaseous halo associated with NGC1399, which extends out to about 90 kpc (Paolillo et al 2002). It appears very asymmetric, consisting of three components that dominate at different scales: the central bright part, coincident with the peak of light; the "galactic" halo that extends out to ∼7 arcmin, which is offset toward the west with respect to the optical galaxy centroid; and, on larger scales, the "cluster" halo that is elongated in the opposite direction.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…The velocity dispersions of the PNe are consistent with the values derived by the star's kinematics and with those for the red GCs (Napolitano et al 2002;McNeil et al 2010). The X-ray data have shown the presence of a hot gaseous halo associated with NGC1399, which extends out to about 90 kpc (Paolillo et al 2002). It appears very asymmetric, consisting of three components that dominate at different scales: the central bright part, coincident with the peak of light; the "galactic" halo that extends out to ∼7 arcmin, which is offset toward the west with respect to the optical galaxy centroid; and, on larger scales, the "cluster" halo that is elongated in the opposite direction.…”
Section: Introductionsupporting
confidence: 85%
“…For R R break , the color map appears asymmetric with respect to the center, and it is more extended and redder on the SW side, where g − i∼1.0-1.2 mag. By comparing the X-ray density contours to the g − i color map, we found a surprising correspondence between the morphology and extension of the "galactic" X-ray halo (see Paolillo et al 2002) on the west side of the galaxy and the color asymmetries observed in the stellar light. In particular, the X-ray contours match the shape of the red tail observed in the inner regions of the galaxy on the west side.…”
Section: Color Profiles and Color Mapmentioning
confidence: 90%
See 3 more Smart Citations